If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X/3-3/2=(2X+9)/3
We move all terms to the left:
X/3-3/2-((2X+9)/3)=0
We calculate fractions
2X/()+(-((2X+9)*2)/()+()/()=0
We calculate terms in parentheses: +(-((2X+9)*2)/()+()/(), so:We get rid of parentheses
-((2X+9)*2)/()+()/(
We add all the numbers together, and all the variables
-((2X+9)*2)/()+1
We multiply all the terms by the denominator
-((2X+9)*2)+1*()
We calculate terms in parentheses: -((2X+9)*2), so:We add all the numbers together, and all the variables
(2X+9)*2
We multiply parentheses
4X+18
Back to the equation:
-(4X+18)
-(4X+18)
We get rid of parentheses
-4X-18
Back to the equation:
+(-4X-18)
2X/()-4X-18=0
We multiply all the terms by the denominator
2X-4X*()-18*()=0
We add all the numbers together, and all the variables
2X-4X*()=0
| 1/2(6-y=y | | -1=-x^2+2x | | 2x-(5-x)=4x-3 | | 10w=6w+12 | | 12x+50+122-3x=180 | | 3(x+2)=2(x10) | | (2x+6)+(2x+6)=(6x−20) | | 1.4-0.05x=0.2x-0.2 | | 56v-7=19+2 | | —18+z=18 | | 3(x+10)+4x=6(4x-1)+2 | | x/8+10=x/4-12 | | x+6+3+18=x(4)/2(7) | | 8x+10=6x+16 | | -3=h+8(2)=4 | | 43=g-39 | | 1/8x+10=1/4x-12 | | 1/8x10=1/4x112 | | b-15=-9 | | -12t-9=-13t-9+10t | | 8x−4=3x+1 | | -2b=-3b-20 | | 19t−12t−5=9 | | 2y+12=-16+4y | | V=3.14(r^2 | | 5x+34=154 | | -u=-10-2u | | −115b+80=−489 | | 5-2x+x=4x-5 | | -8x^2+400x-40000=0 | | -4+7f=-10+7f+f | | 2.3+7.7x2= |